1999
DOI: 10.1523/jneurosci.19-22-10164.1999
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characteristics of Response Integration Evoked by Multiple Whisker Stimulations in the Barrel Cortex of Rats

Abstract: We investigated the responses of 114 cells in the barrel cortex of rats to describe the temporal characteristics of excitatory interactions among neurons serving two vibrissae. To examine these interactions, the principal whisker and one adjacent whisker in the same row were stimulated simultaneously or serially at various interstimulus intervals (ISIs). In 37% of the cells tested, combined stimulation of two whiskers exhibited response facilitation; the response to the combined stimulus was larger than the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
97
3
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 39 publications
15
97
3
1
Order By: Relevance
“…Additionally, unit recording (ArmstrongJames and Fox 1987;Simons 1978) and optical imaging (Kleinfeld and Delaney 1996) studies have reported activity patterns in the barrel cortex following single-whisker deflections elongated along rows. In line with those results, electrophysiological investigations have mainly tested multi-whisker integration along rows (Carvell and Simons 1988;Shimegi et al 1999Shimegi et al , 2000Simons 1985;Simons and Carvell 1989; but see also Mirabella et al 2001). However, a supralinear interaction most prominent for whiskers located in the same arc was recently described (Ghazanfar and Nicolelis 1997), suggesting that modulatory influences could exist both in the rostrocaudal and dorsoventral directions.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Additionally, unit recording (ArmstrongJames and Fox 1987;Simons 1978) and optical imaging (Kleinfeld and Delaney 1996) studies have reported activity patterns in the barrel cortex following single-whisker deflections elongated along rows. In line with those results, electrophysiological investigations have mainly tested multi-whisker integration along rows (Carvell and Simons 1988;Shimegi et al 1999Shimegi et al , 2000Simons 1985;Simons and Carvell 1989; but see also Mirabella et al 2001). However, a supralinear interaction most prominent for whiskers located in the same arc was recently described (Ghazanfar and Nicolelis 1997), suggesting that modulatory influences could exist both in the rostrocaudal and dorsoventral directions.…”
Section: Introductionmentioning
confidence: 70%
“…First, we calculated the facilitation index (FI) proposed by Shimegi et al (1999Shimegi et al ( , 2000. The FI is the ratio between the observed response to the combined deflection of whiskers and the sum of responses to individual deflections calculated on the same time window.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of authors try to support a compulsory convention of waves classification in frequency ranges, which took the attention of Jus et al (1954), Creutzfeldt et al (1966), Eckhorn (1993), Shimegi (1999), and also Wypych et al (2004). However, Saito et al (2005) give the ranges of rhythms of cortical origin according the follow ing criteria: alpha waves (α) in a range (8-12,9) Hz, beta (β) in a range (14,1-25}Hz, theta (θ) in a range (4-7,9) Hz, and delta (δ) in a range (1-3,9) Hz.…”
Section: Determination Of a Normal Reaction Of The Cerebral Cortex Bimentioning
confidence: 99%